Brain capillary geometry development for multiscale modelling study - Shabudin, Abbas; Maryah Harzarina, Jasni; Mohd Jamil, Mohamed Mokhtarudin (IET, 2022)
Due to low spatial resolution of functional magnetic resonance imaging (fMRI), mathematical modelling of human brain is usually developed in ischaemic stroke study in order to enhance the understanding of ischaemic stroke mechanism so that proper treatment plan can be decided to a particular stroke patient. A 3D brain geometry is developed in this project using AutoLISP, which is a programming language within AutoCAD. The objective of this project is to re-create the geometry developed by El-Bouri et al. by replacing the 1-dimensional line with 3-dimensional capillary which can be meshed for the simulation. Simulation of blood flow using Stokes' cell equation is done in the 3D geometry in order to obtain effective hydraulic conductivity, K. Finally, the hydraulic conductivity obtained from the simulation is analysed and compared with previous work done by El-Bouri et al. Based on result in section 3, the initial geometry developed is further modified by adding few small cylinders and also bigger volume of the geometry with 15.21% percentage difference. Non-diagonal elements obtained in matrix K show non-zero values due to small voxel size used for the simulation (180µm), which should be increased to more than 250µm. The percentage difference of diagonal elements K 11 , K 22 , and K 33 are 8.05%, 2.65% and 21.43% respectively. The large percentage differences are probably due to additional volume added to the 3D geometry to maintain its periodicity with neighbouring voxels. Besides, meshing process and mesh size chosen are also contributing factor to the large percentage difference between both hydraulic conductivity values.